Bibliometric analysis of transforaminal lumbar interbody fusion: research status, trends, and future directions - Xun Wang; Aiqi Zhang; Wenchao Yao; Haiyan Qiu; Fabo Feng (EFORT Open Reviews, 2023)
Purpose: Transforaminal lumbar interbody fusion (TLIF) is a classic surgical procedure for posterior lumbar fusion. This study aims to analyze the TLIF field by bibliometric method and comprehensively summarize the research status and trends. Methods: All TLIF-related articles were retrieved from the Web of Science. The data were analyzed using R software and SPSS to calculate corresponding indicators. Visualizations were drawn using VOSviewer and Scimago Graphica, including country, institution, journal, author, and keywords. Results: A total of 919 articles were included. The annual publication volume of TLIF-related articles presented an exponential growth. North America, Europe, and Asia were the main sources of articles, with the USA and China being the main contributors and the USA being the global research center for TLIF. The level of the national economy was an important factor affecting TLIF-related research. The highest number of contributions in this field was made by Kern Singh among authors and by Rush University among institutions. The European Spine Journal was the most influential journal. The research focus has gradually shifted from perfecting the TLIF technique toward emphasizing the patient level. The improvement of minimally invasive techniques and how to improve clinical outcomes as well as accelerate postoperative rehabilitation of patients may be the hot spot of future research. Conclusions: With the advancement of medical technology and the popularization of minimally invasive concepts in recent years, TLIF and its derivative technologies have attracted increasing attention. Patient-centered minimally invasive surgery is a hot research topic in the field of TLIF currently and will continue to be so into the future